2000
DOI: 10.1111/1475-4983.00121
|View full text |Cite
|
Sign up to set email alerts
|

The Cenozoic Brachiopods of the Carnarvon Basin, Western Australia

Abstract: The Paleocene‐Miocene deposits of the Carnarvon Basin of Western Australia contain a rich fauna of brachiopods, but only two species, Tegulorhynchia boongeroodaensisWestralicrania allani, both from the Paleocene, have previously been described.One new genus, Giraliathyris, and eight new species are described herein. They are Giraliathyris mcnamari, G. kaitrinae, G. jubileensis, Liothyrella longorum, Victorithyris decapello, V. cardabiaensis, V. blakeorum, V. tulkiensis, Diedrothyris cf. johnstonianaParaldingi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Craig (1997) reinstated Westralicrania and proposed a second species, W. zenobiae from Albany, Western Australia. Bassett (2000) again synonymised the genus Westralicrania with Danocrania; however, Craig (2000Craig ( , 2002 continued to use Westralicrania. Craig (1997) indicated that new species W. zenobiae is generally larger with a longer pseudointerarea than W. allani; the pseudointerarea is anacline whereas it is apsacline in W. allani; and the spines in W. zenobiae are shorter and radiate in lines whereas in W. allani they are randomly placed.…”
Section: Methodsmentioning
confidence: 99%
“…Craig (1997) reinstated Westralicrania and proposed a second species, W. zenobiae from Albany, Western Australia. Bassett (2000) again synonymised the genus Westralicrania with Danocrania; however, Craig (2000Craig ( , 2002 continued to use Westralicrania. Craig (1997) indicated that new species W. zenobiae is generally larger with a longer pseudointerarea than W. allani; the pseudointerarea is anacline whereas it is apsacline in W. allani; and the spines in W. zenobiae are shorter and radiate in lines whereas in W. allani they are randomly placed.…”
Section: Methodsmentioning
confidence: 99%
“…Representatives of these genera display cardinal processes which, otherwise rare in terebratulidines, are quite polymorphic as regards their myophores, which are massive, high and hypertrophically developed (often trilobed) in Carneithyris (Asgaard 1975;Farrow and Owen 1980;Gaspard 2002) and forming a protuberant cup in Giraliathyris (Craig 2000). Carneithyris subregularis too shows a cardinal process of a characteristic shape (see details in the description).…”
Section: Palaeoecologymentioning
confidence: 99%
“…-This short−looped genus is very common in the Cenozoic strata of New Zealand (Thomson 1916;Allan 1932;Lee 1978;MacKinnon et al 1993;MacFarlan et al 2009), Australia (Craig 2000(Craig , 2001 and Antarctica (Owen 1980;Bitner and Pisera 1984;Wiedman et al 1988;Bitner 1996;Bitner and Crame 2002). It was also reported from the lower part of the Polonez Cove Fm, Low Head Mb (Bitner and Pisera 1984;Bitner 1997;Quaglio et al 2008).…”
Section: Chlamysmentioning
confidence: 99%